2004
DOI: 10.1046/j.1442-9071.2004.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Case Notes

Abstract: Castleman's disease, also known as angiofollicular lymphoid hyperplasia, is a lymphoproliferative disorder that is generally benign. The lesions most commonly originate in the lymph nodes of the mediastinum. The second documented case of Castleman's disease of the lacrimal gland is reported in an 84-year-old woman who presented with an 8-year history of a left upper lid mass. This was excised via a lateral orbitotomy, and a diagnosis of Castleman's disease was made histologically. Relevant images of the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…MCD is a systemic lymphoproliferative disorder that can lead to mass lesion formation in various parts of the body, including the lungs, kidneys, and extranodal sites. Although orbital tissue involvement is relatively rare due to the lack of lymphatic components, previous cases of MCD affecting the lacrimal gland have been reported [ 8 , 9 ]. Venizelos et al reported that orbital involvement might be the initial clinical presentation of CD and those with unicentric hyaline-vascular CD cases showed no association with systemic symptoms and were rarely recurrent [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCD is a systemic lymphoproliferative disorder that can lead to mass lesion formation in various parts of the body, including the lungs, kidneys, and extranodal sites. Although orbital tissue involvement is relatively rare due to the lack of lymphatic components, previous cases of MCD affecting the lacrimal gland have been reported [ 8 , 9 ]. Venizelos et al reported that orbital involvement might be the initial clinical presentation of CD and those with unicentric hyaline-vascular CD cases showed no association with systemic symptoms and were rarely recurrent [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Castleman disease of the lacrimal glands is extremely rare, but unfortunately the serum IgG4 levels have not been reported in the earlier cases. 7 10 Because the signs and the symptoms of both diseases may overlap, clinicians should examine the serum IgG4 levels in patients with Castleman disease routinely. 2 – 5…”
Section: Discussionmentioning
confidence: 99%
“…Unicentric CaD confined to the orbits has been successfully treated with surgical excision in multiple cases [195][196][197][198][199]. Algorithms for the treatment of multicentric CaD have not been established.…”
Section: Castleman's Diseasementioning
confidence: 99%